Effect of extraction temperature on value-added biopolymer recovery in waste activated sludge - Yingjie Yang; Hao Zhou; Wanliang Liu; Kun Wang; Tong Yu (Water Cycle)
Extraction temperature is one of the basic factors for alginate-like exopolymers (ALE) recovery from waste activated sludge (WAS). Given the rising interest in sustainable resource recovery and the promising industrial applications of ALE, this study systematically evaluated the effects of extraction temperatures (50–95 °C) on the ALE yield, profit, compositions, structural properties and sludge reduction. The increasing extraction temperature significantly enhanced ALE yield (from 148.3 mg/g VSS at 80 °C to 218.6 mg/g VSS at 95 °C) and net profit (from 0.441 to 1.046 CNY/kg SS). The elevated temperatures notably increased protein yields compared to polysaccharides. Fluorescence spectroscopy also indicated a pronounced increase in aromatic protein-like substances (C1), whereas polysaccharides showed a comparatively modest increase. Meanwhile, UV–Vis analysis demonstrated decreased E2/E3 and E2/E4 ratios at higher temperatures, suggesting increased humification and reduced molecular weight. Structural analysis showed ALE gels extracted at higher temperatures became denser with decreased mechanical strength (compressive modulus declined from 1.45 MPa at 50 °C to 0.11 MPa at 95 °C). Furthermore, sludge reduction reached 19.8% at 95 °C, significantly alleviating disposal cost of the sludge. These findings in this study provided critical insights for optimizing ALE extraction processes, promoting sludge resource recovery for practical applications.